Hubungan Antara Peningkatan Angka Persalinan Seksio Caesar Dengan Program Jampersal Di Rsud Moewardi Surakarta - Nurrochmad, Agus, Winarsih Nur Ambarwati, S.Kep, Ns, ETN, M.Kep (2014)
Background: in Moewardi hospital Surakarta patients with caesarean section deliveries in 2011 and 2012 has increasedsignificantly. In 2011 as many as 512 patients, and in 2012 as many as 1688 patients. In 2012 has increased very high. According to the training hospitals Moewardi increase in caesarean section deliveries is because since the program Jampersal. With jampersal all people can get the service delivery in the hospital for free. Objective: The purpose the study was to determine the relationship between caesarean section deliveries with programs jampersal in Moewardi hospital Surakarta. Method of study: This research is a quantitative study using a description correlation design. The population in this study a total of 2.200 people with a accidental sampling technique. Number of samples is 220. Analysis tools used by the Chi-Square test ( 2 x ). Result: Result reveal that : 1) the incidence of cesarean deliveries in hospital Dr. Moewardi of years 2011 was 23,2% in 2012 while experiencing increased to 76,8%; 2) level of assurance delivery on maternal 2011-2012 in Moewardi hospitals Surakarta is known that 75% using jampersal and 25% not use jampersal; 3) indication of caesarean section on maternal Moewardi hospital Surakarta in 2011-2012 known that 50,9% do deliveries by caesarean section on maternal indication, 25,5% perform caesarean section based on indications of children and 23,6% perform caesarean section based on indications uteroplacental; Conclusions : based on the result of the chi square test was result shows that the p < 0,05then H0 is rejected. There is a relationship between increased of caesarean section deliveries whit program jampersal in Moewardi hospitals Surakarta.